Analysis of biological control of cassava pests in Africa: I. Simulation of carbon, nitrogen and water dynamics in cassava - Gutiérrez, A.P.; Wermelinger, B.; Schulthess, F.; Baumgaertner, J.U.; Herren, H.R.; Ellis, C.K.; Yaninek, John S. (1988)
( 1 ) A model for the growth and development of cassava, Manihot esculenta Crantz, as modified by weather, soil nitrogen and water is described, and used in later papers to evaluate damage by exotic cassava pests and the effectiveness of control by natural. (2) Analogous relationships between trophic level models at the population and per capita levels were exploited to develop a model that has a common mathematical form across trophic levels enemies. (3) The distributed delay model of Manetsch (1976) was used as the conceptual shell in describing the population dynamics of populations and of organism organ levels (e.g. leaves of plants, ova in animals). (4)The Frazer-Gilbert functional response model from animal ecology was modified to predict rates of photosynthesis and nitrogen and water uptake in plants. (5)Dry-matter partitioning in cassava as affected by solar radiation, temperature, and water and nitrogen stress was simulated and compared with three sets of field data.